Discovering presence as part of nurse educators’ role modelling at a public nursing college in the North West province - Tiisetso A. Mofokeng (AOSIS, 2021)
Background: Nursing students learn the science and art of nursing, including presence, from classroom content, using skills in practice, or by watching an experienced nurse interact with a patient. Nursing education must be designed so that nursing students can construct the art and science of nursing practice. Nursing students must be educated to be sound practitioners in the ‘being’ of nursing practice. Nurse educators modelling presence to nursing students will improve the quality of patient care during clinical training and throughout their professional role.